Sensitivity Analysis of Banana Chips Small Business - Pudjiastuti, Agnes Quartina; Iriani, Nur Ida; Sa’diyah, Ana Arifatus (CAKRAWALA, 2018)
Banana chips are one of the traditional foods favored by Indonesian people and are mostly cultivated on a small scale. This study aims to analyze the feasibility and sensitivity of banana chips business. Primary data to compile cash flow in 2017 was obtained from small business of banana chips which was then analyzed feasibility financially. Sensitivity analysis was based on the increase in total cost and decreased production. The results of the analysis show that existing banana chips business was categorized as feasible based on the criteria of gross B/C, net B/C, NPV and IRR. The banana chips business was still feasible even though the total cost increased by 5% and production decreased by 15%.